Administrative elites: autonomy or submission? - Pankov, Irena (Journal of the Belarusian State University. Sociology, 2019)
The results of the study aimed at learning the formation of administrative elite in modern Poland are submitted. Special attention is paid to the interaction between the politics and public officials. The objectives and duties of the administrative elite are shown from the viewpoint of the latter. The empiric basis of the analysis is 50 in-depth interviews carried out in 2013 with the directors and deputy directors of the departments in Polish ministries.